Humus content and quality under different soil tillage systems - Ľubica Pospíšilová; Naděžda Fasurová; Veronika Petrášová (Soil and Water Research, 2010)
The main objective of our study was to compare the contents and quality of humic substances in selected soil types under different tillage regimes (deep, reduced, minimum). Non destructive spectroscopic methods such as UV-VIS and synchronous fluorescence spectroscopy were applied. After three years of experiments, no statistically significant differences in the total carbon content, labile carbon content, and humic substances carbon content were found. Humic substances quality and the absorbance in UV-VIS spectral range was the highest in Haplic Chernozem (minimum tillage). Fluorescence intensity varied in dependence on the soil types, however, the same main fluorophores in all samples were detected. Fluorescence of humic substances was the highest in Haplic Chernozem (minimum tillage). The determination of HS spectroscopic characteristics was found as a sensitive indicator for HS quality assessment.